BRITISH RECORDING AUDIO SEBAGAI MEDIA TERHADAP PEMAHAMAN MENDENGARKAN SISWA KELAS XI SMA NEGERI 3 MAKASSAR 2021 - Rochaeti, Titin; Fansury, Andi Hamzah; Sahib, Nurfaizah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
The objective of the research is to know the influence of British Recording Audio as a media towards students listening comprehension at theeleventh grade of SMA Negeri 3 Makassar.In this study the writer used quantitative research to find the data and results of tests that have been done by the writer to see the ability of the students in understanding their listening. This research was conducted on December, 8th2020at the Eleventh grade of SMA Negeri 3 Makassar, in the academic year 2020/2021. The population of this research was Eleventh-Grade students of SMA Negeri 3 Makassar which of 270 students divided into nine classes which each class consists of approximately 30 students. The writer took 11 grade class which consisted of 30 students. The writer choose sample randomly depends on student’s comprehension in listening. Based on research findings shows that the value of mean score in pre-test was 47 and posttest was 67. The t-test of this research was 19.287 was higher than t-table 1.697 with the significance 0,05. It means that British Recording Audio had a significance influenced towards students listening comprehension at the third-grade of SMA Negeri 3 Makassar. Based on the research conducted at SMA Negeri 3 Makassar, it can be concluded that there is a significant difference teaching student using British Recording Audio in listening comprehension for the eleventh-grade students of SMA Negeri 3 Makassar in academic year 2020/2021. It can be seen based on the student’s post-test scores in teaching listening is higher than the student’s post-test scores using British Recording Audio